Mechanosensitive Ca2+ Release from Intracellular Stores in Nitella flexilis - Kikuyama, Munehiro; Tazawa, Masashi (Plant and Cell Physiology, 2001)
We found previously that the cytoplasmic drop isolated from internodal cells of Nitella flexilis releases Ca2+ in response to hypotonic treatment and named the phenomenon hydration-induced Ca2+ release (HICR). The HICR is assumed to be a result of activation of Ca2+ permeable channels in the membrane of Ca2+ stores in a stretch-activated manner. To prove this idea, mechanical stimulus was applied to the drop by means of shooting isotonic/hypnotic medium or silicon oil into the drop, or compressing the drop. All these mechanical stimuli induced a rapid increase in the Ca2+ concentration of the drop. The chloroplast fraction isolated from the cytoplasmic drop released Ca2+ on compression, while the chloroplast-free cytoplasm did not. In Chara corallina , the cytoplasmic drop, which shows a very weak HICR, also responded weakly to the mechanical stimulus, but the chloroplast fraction was inert. When chloroplasts from Chara were added to the chloroplast-free cytoplasm of N. flexilis , the cytoplasm recovered the mechanoresponse. Starch grains were as effective as chloroplasts. The data indicate that Ca2+ permeable channels in the membrane of Ca2+ stores in N. flexilis are really mechano-sensitive.